Metahistoria Imaginación histórica en la Europa del siglo XIX - WHITE, Hayden (FONDO DE CULTURA ECONOMICA, 1998)
Contenido : RANKE, LEOPOLD VON; TOCQUEVILLE, ALEXIS DE; BURCKHARDT, JACOB; MARX, KARL; NIETZSCHE, FRIEDRICH; CROCE, BENEDETTO